Molecular characteristics of dissolved organic matter in the porewater of "Challenger" Deep sediments, Mariana Trench - Zheng, Kexin; Hu, Tingcang; Luo, Min; Chen, Linying; Qi, Yulin; Xie, Jingqian; Chen, Duofu (Frontiers in Marine Science, 2024)
Hadal trenches (>6,000 m water depth) have been revealed as hotspots of organic carbon deposition and mineralization. Here, we present the molecular compositions of porewater dissolved organic matter at the "Challenger" Deep (Site MT02; 10,954 m water depth) sediments of the Mariana Trench and the adjacent abyssal plain sediments (Site MT04; 5,437 m water depth) using ultra highresolution Fourier Transform Ion Cyclotron Resonance Mass Spectrometry (FT-ICR MS). The Challenger Deep sediments are characterized by higher abundance of recalcitrant compounds, mainly composed of highly unsaturated compounds (79.7%) and carboxyl-rich alicyclic molecules (57.1%), compared to the abyssal plain sediments (68.3%&51.5%). Principal component analysis suggests that TOC content in the sediments exerts an important control on the molecular characteristics of porewater DOM. It is likely that higher TOC content triggers elevated microbial-mediated organic matter mineralization, thereby forming more refractory organic matter compounds. These results improved the knowledge of the poorly-understood DOM compositions and microbial organic matter degradation in the ultra-deep, extreme ocean environment.